Evaluation of anti-nociceptive and anti-inflammatory activities of Piper sylvaticum (Roxb.) stem by experimental and computational approaches - Chy M.N.U.; Adnan M.; Rauniyar A.K.; Amin M.M.; Majumder M.; Islam M.S.; Afrin S.; Farhana K.; Nesa F.; Sany M.A.; Tanim M.A.H.; Siddique T.I.; et al. (Springer Netherlands, 2022)
Piper sylvaticum Roxb., (Family: Piperaceae), commonly known as pahaari peepal, is used in traditional medicine for the treatment of rheumatic pain, headache, asthma, chronic cough, diarrhea, and wounds. To provide scientific proof for its traditional use, the present study was designed to investigate the antinociceptive and anti-inflammatory properties of methanol extract of P. sylvaticum stem (MEPSS) in pain models. Additionally, computational studies viz. molecular docking, ADME and toxicological property predictions were performed to identify the potent phytochemicals of this plant for antinociceptive and anti-inflammatory activities with good oral bioavailability and safety features. Quantitative phytochemical analysis of MEPSS was performed using established protocols. The antinociceptive activity was determined using acetic acid and formalin test in mice at the doses of 200 and 400 mg/kg while paw edema induced by carrageenan used for anti-inflammatory activity. Molecular docking study was performed by Schrödinger Maestro 10.1 whereas the SwissADME and admetSAR were used for ADME and toxicity prediction respectively. The total phenolic and flavonoid contents of MEPSS were 93.39 and 53.74 mg gallic acid and quercetin equivalent/g of extract respectively. The methanol extract exhibited significant and dose-dependent antinociceptive and anti-inflammatory effects in experimental pain models. Also, our docking study showed that piperine, piperlonguminine, and sylvamide have the best binding affinities to cyclooxygenase enzymes with good ADME/T properties. This study confirmed that MEPSS possess significant antinociceptive and anti-inflammatory activities which could be due to the presence of phytochemicals and three bioactive compounds (piperine, piperlonguminine, and sylvamide) were found to be most effective in computational studies.